Does the innate relative size of the humeral head and glenoid affect the risk of anterior shoulder instability? - Willigenburg, NW (Shoulder Elbow, 2018)
BACKGROUND: Bony lesions after shoulder dislocation reduce the joint contact area and increase the risk of recurrent instability. It is unknown whether the innate relative sizes of the humeral head and glenoid may predispose patients to shoulder instability. This study evaluated whether anterior shoulder instability is associated with a larger innate humeral head/glenoid ratio (IHGR). METHODS: We evaluated CT scans of 40 shoulders with anterior shoulder instability and 48 controls. We measured axial humeral head diameter and glenoid diameter following native contours, discarding any bony lesions, and calculated IHGR by dividing both diameters. Multivariate logistic regression determined whether the IHGR, corrected for age and gender as potential confounders, was associated with anterior shoulder instability. RESULTS: Mean IHGR was 1.48 ± 0.23 in the group with anterior shoulder instability and 1.42 ± 0.20 in the group without anterior shoulder instability. Measurements for axial humeral head and axial glenoid diameters demonstrated excellent intra-rater reliability (ICC range: 0.94–0.95). IHGR was not significantly associated with anterior shoulder instability (OR = 1.105, 95%CI = 0.118–10.339, p = 0.930). DISCUSSION: The innate ratio of humeral head and glenoid diameters was not significantly associated with anterior shoulder instability in this retrospective sample of 88 shoulder CT scans.